Increasing the efficiency of harmonic generation by nonlinear scatterers - Лучанинов, Анатолий Иванович; Гавва, Дмитрий Сергеевич; Уайд, Сальман Рашид (Eastern-European Journal of Enterprise Technologies, 2014)
Scatterers, which have the elements with nonlinear properties (nonlinear scatterers (NS)) in their structure were considered. Primary attention is paid to NS, used to implement the antennas with frequency multiplication. For them, the main requirement is increasing the NS emission efficiency by any of the selected harmonics. The aim of the research was to find technical solutions of NS that, by choosing the design and parameters of the emitter, would ensure efficient conversion, required directional characteristics and easy implementation of NS. It was shown that for series Schottky diodes, operating in the resistive nonlinearity mode, at changing active resistance of the emitter within (25 ... 800) ohms, maximum conversion factor will be the achieved in the case when the ratio of the emitter active resistance on the second harmonic to the resistance on the first harmonic is within 0,25....0,5. For diodes, operating in the capacitive nonlinearity mode, values of the active component of the input resistance of the NS emitter at the fundamental frequency, at which the conversion factor reaches a maximum, should be of about 5...20 ohms, while at the second-harmonic frequency, the resistance should be 2...4 times less than at the excitation frequency. By selecting the type of the emitter and its geometrical dimensions, it was shown that it is possible to create both single NS and lattices based on them with the conversion factor, close to the maximum possible for nonlinear elements, used in them (the value of the conversion factor of nonlinear scatterer of about 90% was obtained in the frequency doubling mode for the capacitive nonlinearity mode). It was shown that NS, based on emitter with displaced feeding point, with a slight loss in the value of the conversion factor compared to the NS, based on more complex emitters provide good performance of large-aperture grids of antennas-multipliers in the broad sector of scanning angles. It was concluded that by selecting the type of the emitter and its size it is possible to create both single NS and lattices based on them with conversion ratio, close to the maximum possible for nonlinear elements, used in them. This allows to simplify the design of the NS grids, having excluded additional matching and filtering devices.